What does the Bank of Japan do to East Asia? - Bartosz Maćkowiak (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
In recent policy debates some have argued that expansionary monetary policy in Japan can increase real output in Japan and in Japan's neighbors, while others have warned that it is a beggar-thy-neighbor policy. In this paper we estimate structural vector autoregressions to assess the effects of Japanese monetary policy shocks. We find that the effects of Japanese monetary policy shocks on macroeconomic variation in East Asia have been modest and difficult to reconcile with the beggar-thy-neighbor view. We estimate that the Asian crisis was preceded by expansionary monetary policy shocks in Japan, but we fail to find support for the view that these shocks contributed to the crisis.
Keywords: 330; Geldpolitik; Schock; Spillover-Effekt; VAR-Modell; Japan; Ostasien